Somatic Sex: On the Origin of Neoplasms With Chromosome Counts in Uneven Ploidy Ranges - Haas, Oskar A. (Frontiers in Cell and Developmental Biology, 2021)
Stable aneuploid genomes with nonrandom numerical changes in uneven ploidy ranges define distinct subsets of hematologic malignancies and solid tumors. The idea put forward herein suggests that they emerge from interactions between diploid mitotic and G0/G1 cells, which can in a single step produce all combinations of mono-, di-, tri-, tetra- and pentasomic paternal/maternal homologue configurations that define such genomes. A nanotube-mediated influx of interphase cell cytoplasm into mitotic cells would thus be responsible for the critical nondisjunction and segregation errors by physically impeding the proper formation of the cell division machinery, whereas only a complete cell fusion can simultaneously generate pentasomies, uniparental trisomies as well as biclonal hypo- and hyperdiploid cell populations. The term “somatic sex” was devised to accentuate the similarities between germ cell and somatic cell fusions. A somatic cell fusion, in particular, recapitulates many processes that are also instrumental in the formation of an abnormal zygote that involves a diploid oocyte and a haploid sperm, which then may further develop into a digynic triploid embryo. Despite their somehow deceptive differences and consequences, the resemblance of these two routes may go far beyond of what has hitherto been appreciated. Based on the arguments put forward herein, I propose that embryonic malignancies of mesenchymal origin with these particular types of aneuploidies can thus be viewed as the kind of flawed somatic equivalent of a digynic triploid embryo.